An analysis on the application of third party guarantee in islamic capital market with special reference to sukuk - Issoufou, Chaibou (Kulliyyah of Law, Internatiional Islamic University Malaysia, 2014)
The application of third party guarantee is drastically becoming a paramount element in Islamic capital market. Its proper application in Islamic capital market has not been researched deeply without specific focus on Sukuk. Therefore, the primary objective of this study is to analyze the application of third party guarantee in Islamic capital market with special reference to various Sukuk such as Sukuk al-Ijarah, Sukuk al-Mudarabah and Sukuk al-Istisna'. The overview of the concept of third party guarantee in Islamic law which includes Muslim jurists' point of views on third party guarantee, its objective in Islamic law, pillars, legality, conditions and its effects on the contracting parties as well as the views of Muslim jurists on charging a fee on the third party guarantee have been explicitly analyzed. The concept of the application of third party guarantee in Islamic capital market and its instruments, Islamic money market and Islamic derivatives, has also been discussed in this study. The methodology used in the study is based on qualitative analysis whereby primary and secondary sources were collected. It was discovered in the study that the application of third party guarantee is permissible in Islamic capital market and its instruments provided that it is done voluntarily. The findings of the study further elaborated that the application of third party guarantee must be done without charging any fee in relation to the guarantee. It was also revealed in the study that the application of third party guarantee is permissible in the processes of Sukuk al-Ijarah, Sukuk al-Mudarabah and Sukuk al-Istisna' without taking any fee in relation to the guarantee. However, in a Sukuk al-Istisna' transaction it is permissible to impose compensation on the manufacturer in case he delays the delivery of the manufactured asset on the due date and that it amounts to cause of damage on the commissioner to manufacture. Finally, the study provides suggestions for an alternative application of third party guarantee in Islamic capital market to the existing one such as having a government of a country to provide a voluntary third party guarantee for the project that Sukuk is issued.